LITERARY EDUCATION OF SCHOOLCHILDREN IN THE CHALLENGES OF COMPETENCE LEARNING - Sytchenko, Anatolii (Educological discourse, 2020)
The article covers the issues of practical implementation of competency learning of Ukrainian literature. Philosophical and pedagogical developments on the problem are analyzed, modern possibilities of modeled learning are highlighted, an important form of which is educational technologies, which are quite relevant in the process of literary education. Improving the effectiveness of learning literature in condition of technological pedagogical process is connected in the study with the formation of ways of mental work that allow pupils independently critically comprehend the works they have read, interpret them with arguments not only perceive the author, but also produce their own meanings, which makes their actions personal significant. The procedural aspect of the problem of competence learning of literature, aimed at the formation of a knowledgeable and skilled, cultural pupil-reader, his value orientations is emphasized. It is argued that the peculiarities of fiction and its study in school cause a positive impact on the balance of technocratic and humanistic factors of modern education, as works of art of word have not only competence potential, but also aesthetic qualities and capabilities, moral and ethical patterns of human behavior. At the same time, the article points out certain risks associated with a number of difficulties that arise in reforming the modern school on the basis of a competency-based approach. The author draws attention to the contradictions between competence and morality; developments in domestic pedagogy and the introduction of foreign models of education; knowledge and skills and ideas and beliefs, the subjective experience of pupils and their educational activities, which exacerbate the problems of school reform, the implementation of a competency-based approach, personality-oriented learning, convince of the need for technologicalization of education. It is first of all about the need to balance the business qualities of a competent specialist with his moral qualities; conditions for transferring foreign educational ideas and projects to the national base; achieving the unity of knowledge, skills and beliefs of the subject of activity; coordination of the content of competencies with the process of their practical implementation. The article is intended for teachers, scientists and students.